Effects of Forearm Compression Sleeves on Muscle Hemodynamics and Muscular Strength and Endurance Parameters in Sports Climbing: A Randomized, Controlled Crossover Trial - Limmer, Mirjam; de Marées, Markus; Roth, Ralf (Frontiers in Physiology, 2022)
Wearing compression garments is a commonly used intervention in sports to improve performance and facilitate recovery. Some evidence supports the use of forearm compression to improve muscle tissue oxygenation and enhance exercise performance. The purpose of this study was to evaluate the immediate effects of forearm compression sleeves on muscular strength and endurance of finger flexor muscles in sports climbers. This randomized crossover study included 24 sports climbers who performed one familiarization trial and three subsequent test trials while wearing compression forearm sleeves (COMP), non-compressive placebo forearm sleeves (PLAC), or no forearm sleeves (CON). Test trials consisted of three performance measurements (intermittent hand grip strength measurements, finger hang, and lap climbing) at intervals of at least 48 h in a randomized order. Muscle oxygenation during hand grip and finger hang measurements was assessed by near-infrared spectroscopy. The maximum blood lactate level, rate of perceived exertion, and forearm muscle pain were also determined directly after the lap climbing trials. COMP resulted in higher changes in oxy[heme] and tissue oxygen saturation (StO2) during the deoxygenation (oxy[heme]: COMP –10.7 ± 5.4, PLAC –6.7 ± 4.3, CON –6.9 ± 5.0 [μmol]; p = 0.014, ηp2 = 0.263; StO2: COMP –4.0 ± 2.2, PLAC –3.0 ± 1.4, CON –2.8 ± 1.8 [%]; p = 0.049, ηp2 = 0.194) and reoxygenation (oxy[heme]: COMP 10.2 ± 5.3, PLAC 6.0 ± 4.1, CON 6.3 ± 4.9 [μmol]; p = 0.011, ηp2 = 0.274; StO2: COMP 3.5 ± 1.9, PLAC 2.4 ± 1.2, CON 2.3 ± 1.9 [%]; p = 0.028, ηp2 = 0.225) phases of hand grip measurements, whereas total [heme] concentrations were not affected. No differences were detected between the conditions for the parameters of peak force and fatigue index in the hand grip, time to failure and hemodynamics in the finger hang, or performance-related parameters in the lap climbing measurements (p ≤ 0.05). Forearm compression sleeves did not enhance hand grip strength, sports climbing performance parameters, physiological responses, or perceptual measures. However, they did result in slightly more pronounced changes of oxy[heme] and StO2 in the deoxygenation and reoxygenation phases during the hand grip measurements.